Project-Based Learning as a Transformative Pedagogical Strategy for Enhing Students’ Skills and Problem-Solving Competence in Educational Institutions - Muhammad Zainullah; Jazilurrahman Jazilurrahman; Umar Manshur (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
To respond to the challenges of 21st-century education and the Industrial Revolution 4.0, students are required to master higher-order thinking skills, including creativity, collaboration, communication, and problem-solving. This study aims to analyze the implementation of Project-Based Learning (PjBL) in improving students’ problem-solving skills within educational institutions. Employing a qualitative approach with a case study design, the research was conducted in two educational institutions with different characteristics. Data were collected through classroom observations, in-depth interviews, documentation, and analysis of students’ project work. The validity of the data was ensured through triangulation techniques and informant verification. The findings reveal that the implementation of PjBL significantly enhances student engagement, learning motivation, and collaborative competencies. Furthermore, it fosters a solution-oriented mindset and reflective thinking among students. The integration of Islamic values within project activities makes learning more contextual and meaningful, positively influencing students’ attitudes and daily behavior. In addition, teachers demonstrate increased creativity and adaptability in managing student-centered learning environments. Overall, PjBL proves to be an effective pedagogical strategy in improving students’ problem-solving skills and aligns well with the principles of the Independent Curriculum. This study contributes practical insights for educators, institutions, and policymakers in designing more relevant, engaging, and value-oriented learning experiences.